Acquired factor V inhibitor - Ang, Ai Leen; Kuperan, Ponnudurai; Ng, Chin Hin; Ng, Heng Joo (Thrombosis and Haemostasis, 2009)
Acquired factor V(FV) inhibitors as a rare bleeding disorder, poses a formidable challenge to treating physicians with limited evidence to guide its management. We systematically reviewed our experience in Singapore and the published literature to determine possible answers to clinical questions formulated on the manifestation and best management of non-bovine thrombin and non-congenital acquired FV inhibitors. The incidence in Singapore was 0.09 cases per million person years (3 cases over 10 years). Seventy-three other cases meeting pre-defined search criteria were found in the published literature. Bleeding occurred in 68.4% of these patients, with mucous membranes being the most common site. Intracranial and retroperitoneal bleeds carried the highest mortality. The mortality rate from bleeding was 12%. There was a tendency for FV levels and PT/aPTT prolongation to predict bleeding but not the inhibitor level. No consistently effective haemostatic agent could be determined, but platelet transfusion should probably be the first line therapy. Among bleeding patients, inhibitors tended to disappear faster with inhibitor elimination therapy (IET) compared to without IET (60 vs. 150 days, p=0.299). IET made no significant difference among non-bleeding patients (p=0.511) and is thus recommended for bleeding patients or those with high bleeding risk. Steroids as single agent IET was effective in the majority of patients. Logical management approaches may be drawn but are limited by small sample size, heterogeneity of reports, and potential publication bias. The inception of a comprehensive registry will provide more reliable data that may verify our findings.
Keywords: Haemostasis; acquired coagulation disorders; management of disease; factor V inhibitors